Coupling of atomic quadrupole transitions with resonant surface plasmons - Chan, Eng Aik (2019)
We report on the coupling of an electric quadrupole transition in atomic vapor with plasmonic excitation in a nanostructured metallic metamaterial. The quadrupole transition at 685 nm in the gas of cesium atoms is optically pumped, while the induced ground-state population depletion is probed with light tuned on the strong electric dipole transition at 852 nm. We use selective reflection to resolve the Doppler-free hyperfine structure of cesium atoms. We observe a strong modification of the reflection spectra at the presence of metamaterial and discuss the role of the spatial variation of the surface plasmon polariton on the quadrupole coupling.